Effects of Diet on Larval Survival, Growth, and Development of the Sea Cucumber Holothuria leucospilota - Zonghe Yu; Hong Wu; Youkai Tu; Zesen Hong; Jiewen Luo (Aquaculture Nutrition)
Because most tropical sea cucumbers have been overexploited around the world, the sea cucumber Holothuria leucospilota has become increasingly commercially important in recent years. Restocking and aquaculture of H. leucospilota using hatchery-produced seeds could both enhance declining wild populations and provide sufficient beche-de-mer product to satisfy increasing market demand. Identifying an appropriate diet is important for successful hatchery culture of the H. leucospilota. In this study, we trialed different ratios of microalgae Chaetoceros muelleri (2.00–2.50×106 cells/mL) and yeast (Saccharomyces cerevisiae, ~2.00×106 cells/mL) in diets for H. leucospilota larvae (6 d after fertilization, referred to as “day 0”) at proportions 4 : 0, 3 : 1, 2 : 2, 1 : 3, and 0 : 4 by volume, in 5 treatments (A, B, C, D, and E, respectively). Larval survival rates in these treatments decreased over time, with the survival highest in treatment B (59.24±2.49%) on day 15 (double that of the lowest rate in treatment E (28.47±4.23%)). For any sampling event, larval body length in treatment A was always the lowest after day 3, and that for treatment B was always the highest, except on day 15. The maximum percentage of doliolaria larvae occurred in treatment B (23.33%) on day 15, followed by treatments C, D, and E (20.00%, 10.00%, and 6.67%, respectively). No doliolaria larvae occurred in treatment A, and pentactula larvae occurred only in treatment B (3.33%). On day 15 in all treatments, late auricularia larvae had hyaline spheres, but these were not prominent in treatment A. Densities of juveniles attaching to settlement plates varied with treatments, and the values were very low for the larvae only fed microalgae (A, 2.39±1.95 ind per plate) or yeast (E, 2.13±1.05 ind per plate)—only ~5% of the maximum number settling in treatment B (45.56±7.24 ind per plate). Increased larval growth, survival and development, and juvenile attachment indicates that diets combining microalgae and yeast are more nutritionally balanced than single diets for hatchery of H. leucospilota. A combined diet of C. muelleri and S. cerevisiae at a 3 : 1 ratio is optimum for the larvae. Based on our results, we propose a larval rearing protocol to facilitate mass production of H. leucospilota.